Design load tables for laterally loaded masonry panels to BS 5628 parts 1 and 2 : (including bed joint reinforced panels) - Cheng, Richard (Thomas Telford, 1996)
Masonry walls are not isotropic; they have less strength in bending in the vertical direction than in the horizontal. The design of two-way spanning masonry panels under lateral loads is complicated. The design tables in this book present a practical approach to the design of rectangular lateral loaded panels under uniformly distributed loads.